2019
DOI: 10.1021/acs.nanolett.9b03779
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer from Perovskite Nanocrystals to Dye Molecules Does Not Occur by FRET

Abstract: Single formamidinium lead bromide (FAPbBr 3) perovskite nanocubes, approximately 10 nm in size, have extinction cross sections orders of magnitude larger than single dye molecules and can therefore be used to photoexcite one single dye molecule within their immediate vicinity by means of excitation-energy transfer (EET). The rate of photon emission by the single dye molecule is increased by 2 orders of magnitude under excitation by EET compared to direct excitation at the same laser fluence. Because the dye ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…The study of the physical properties of MH NCs is a vivid field of research relying on various continuous-wave and time-resolved optical spectroscopies performed under controlled temperature [55][56][57][58][59][60] and environmental conditions [61][62][63] at both the ensemble and the single-particle level (Figure 4) [64][65][66][67]. This enables us to build a comprehensive photophysical picture including the bandgap energy [20,27], the emission spectrum and its excitonic versus defect/dopantbased contributions [6,[68][69][70][71][72], the exciton [73] and biexciton binding energies [74], and the rates of radiative and nonradiative processes in single NC and ensembles [75][76][77] and in hybrid architectures [78][79][80][81][82], as well as the extent of blinking processes and single-photon emission properties [64][65][66][67] (Figure 4). Overall, this information offers design guidelines for the engineering of perovskite NCs with optical properties tailored for specific applications.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…The study of the physical properties of MH NCs is a vivid field of research relying on various continuous-wave and time-resolved optical spectroscopies performed under controlled temperature [55][56][57][58][59][60] and environmental conditions [61][62][63] at both the ensemble and the single-particle level (Figure 4) [64][65][66][67]. This enables us to build a comprehensive photophysical picture including the bandgap energy [20,27], the emission spectrum and its excitonic versus defect/dopantbased contributions [6,[68][69][70][71][72], the exciton [73] and biexciton binding energies [74], and the rates of radiative and nonradiative processes in single NC and ensembles [75][76][77] and in hybrid architectures [78][79][80][81][82], as well as the extent of blinking processes and single-photon emission properties [64][65][66][67] (Figure 4). Overall, this information offers design guidelines for the engineering of perovskite NCs with optical properties tailored for specific applications.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…Blending high photoluminescence quantum yield (PLQY) perovskite emitters with molecules such as oligomer, polymer, or other organics to obtain a single emitting layer provides a seemingly direct approach to achieve efficient white electroluminescence. However, the undesired ET which arises because of the close proximity of the two emitting species results in blue emission quenching and consequently reduces the probability of white light generation. , The potential of layered broadband emitting perovskites , as single emitters for white light emission, on the other hand, is surrounded by issues pertaining to low PLQY, spectral instability, , and poor charge transport, thus limiting their practical application in LEDs. Moreover, with the ET process known to be increasingly more efficient with decreasing intermolecular distances, , it is hardly surprising that reports on white electroluminescent devices, particularly those based on perovskites, still remain largely limited (Table ).…”
mentioning
confidence: 99%
“…[83] Optical spectroscopy studies employing perovskite QDs and surface-bound organic dyes showed that excitation energy transfer dominates over Förster resonance energy transfer. [84][85][86] PL intensity traces obtained at the single particle level demonstrated that excitation energy transfer from the QDs to acceptor molecules can efficiently suppress QD PL elongating the OFF-periods. [84] Organic dyes that may act as excitation energy transfer acceptors for perovskite QDs include naphthalene and tetracene derivates, [85] various polycyclic aromatic hydrocarbons, [87] rhodamine B, [86] and perylene dyes.…”
Section: Next Generation Of Qds For Smlm Applicationsmentioning
confidence: 99%
“…[84][85][86] PL intensity traces obtained at the single particle level demonstrated that excitation energy transfer from the QDs to acceptor molecules can efficiently suppress QD PL elongating the OFF-periods. [84] Organic dyes that may act as excitation energy transfer acceptors for perovskite QDs include naphthalene and tetracene derivates, [85] various polycyclic aromatic hydrocarbons, [87] rhodamine B, [86] and perylene dyes. [88] In all these approaches, the transfer rates can be adjusted by the relative energy level alignment and the donor (QDs) [79,83,85,86,89] -acceptor (molecules) distance.…”
Section: Next Generation Of Qds For Smlm Applicationsmentioning
confidence: 99%